Depression as a risk factor for osteoporosis independent of sarcopenia in hemodialysis patients: findings from a multicenter cross-sectional study - Hu, Xiaohua; Ye, Xianwu; Chen, Haimin; Wu, Bibo; Guo, Qi; Yu, Chen; Ding, Wei; Niu, Jianying; Zhao, Junli; Qi, Hualin; Zhang, Suhua; Xue, Cheng; et al. (BMC nephrology, 2025)
Osteoporosis and sarcopenia frequently occur in patients with end-stage renal disease undergoing hemodialysis (HD), and depression is also a common mental health issue in this population. Despite the prevalence of these conditions, the interrelationships among them remain poorly understood in HD patients. In this multicenter cross-sectional study, 858 HD patients from 7 dialysis centers were recruited. Bone mineral density (BMD) was assessed using dual-energy X-ray absorptiometry. Skeletal muscle mass index (SMI) was calculated from body composition data obtained through multifrequency bioimpedance analysis (BIA), while handgrip strength (HGS) was measured with a dynamometer. Gait speed was evaluated with a 4-meter walk test, and depression was assessed using the Patient Health Questionnaire-9 (PHQ-9). Among the 858 participants (524 men, 334 women), 39.2% had osteoporosis. The prevalence of sarcopenia and depression was 18.9% and 42.1%, respectively. Logistic regression analysis showed that SMI was significantly associated with a decreased risk of osteoporosis (OR = 0.638, 95% CI = 0.494-0.823, P = 0.001), while HGS was not(OR = 0.990, 95% CI = 0.963-1.017, P = 0.449). HD patients with sarcopenia were 1.92 times more likely to have osteoporosis than those without sarcopenia. Most notably, after adjusting for both sarcopenia and SMI, the risk of osteoporosis in HD patients with depression was 1.45 times higher than in those without depression (OR = 1.452, 95% CI = 1.060-1.989, P = 0.020). In HD patients, increased muscle mass, rather than muscle strength, is linked to a lower risk of osteoporosis. Notably, depression emerges as a significant risk factor for osteoporosis in this population, highlighting the need for mental health considerations in managing bone health.